2016
DOI: 10.1186/s40795-016-0045-y
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition knowledge, attitudes and practices among healthcare workers in management of chronic kidney diseases in selected hospitals in Dar es Salaam, Tanzania; a cross-sectional study

Abstract: Background: Chronic kidney disease (CKD) is a global public health problem. All health care professionals need to be knowledgeable and competent in nutrition as it applies to health promotion, prevention and treatment of acute and chronic diseases. Nutrition intervention is an important component in optimizing diet among CKD patients. However, there is limited information on the nutrition knowledge on management of CKD among healthcare workers in Dar es Salaam Tanzania. This study assessed nutrition knowledge,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
21
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 17 publications
8
21
1
Order By: Relevance
“…However, little is known about the knowledge base or impact of non‐dietetic nephrology staff providing dietary advice to patients. Only two small surveys have been published and these indicate that the nutrition knowledge of renal health professionals (such as nurses and doctors) was suboptimal . This is of concern because many health professionals believe they have a significant role in the provision of dietary advice to patients with chronic disease .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, little is known about the knowledge base or impact of non‐dietetic nephrology staff providing dietary advice to patients. Only two small surveys have been published and these indicate that the nutrition knowledge of renal health professionals (such as nurses and doctors) was suboptimal . This is of concern because many health professionals believe they have a significant role in the provision of dietary advice to patients with chronic disease .…”
Section: Discussionmentioning
confidence: 99%
“…Only two small surveys have been published and these indicate that the nutrition knowledge of renal health professionals (such as nurses and doctors) was suboptimal. 48,49 This is of concern because many health professionals believe they have a significant role in the provision of dietary advice to patients with chronic disease. 50 Furthermore, findings from a study of patients receiving dietary advice for cardiac rehabilitation indicated that patients stopped following dietary recommendations after receiving contradictory advice from other health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses who work in renal units with a good or moderate knowledge level play an important role in patient education. 27 In our study, the overall nurses' knowledge related to the nutritional management of renal failure was fair. The majority of nurses (70.6%) had fair knowledge score and (17.6%) had a good knowledge score.…”
Section: Resultsmentioning
confidence: 63%
“…Instead, nurses who had fewer years of experience had a higher knowledge score. The study performed by Munuo et al 27 recognized Discussion that the knowledge level is not related to the increase in working experience. Similar results were found in another evaluation study, which was conducted among licensed nurses working at a nursing home in the United States.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation